Polarizability is a key parameter for molecular electronics. Issue 3 (28th January 2021) - Gillet, Angélique; Cher, Sébastien; Tassé, Marine; Blon, Thomas; Alves, Sandra; Izzet, Guillaume; Chaudret, Bruno; Proust, Anna; Demont, Phillipe; Volatron, Florence; Tricard, Simon
Abstract : Conducting AFM measurements on self-assemblies of platinum nanoparticles including polyoxometalates show that the polarizability of the molecules is a key parameter to consider electron transport. Abstract : Identifying descriptors that govern charge transport in molecular electronics is of prime importance for the elaboration of devices. The effects of molecule characteristics, such as size, bulkiness or charge, have been widely reported. Herein, we show that the molecule polarizability can be a crucial parameter to consider. To this end, platinum nanoparticle self-assemblies (PtNP SAs) are synthesized in solution, including a series of polyoxometalates (POMs). The charge of the POM unit can be modified according to the nature of the central heteroatom while keeping its size constant. POM hybrids that display remote terminal thiol functions strongly anchor the PtNP surface to form robust SAs. IV curves, recorded by conductive AFM, show a decrease in Coulomb blockade as the dielectric constant of the POMs increases. In this system, charge transport across molecular junctions can be interpreted as variations in polarizability, which is directly related to the dielectric constant.